The Implementation of Flipped Classroom Learning Model in Teaching Paragraph Writing - Miftahul Rachmat; Liliana Muliastuti; Emzir Emzir (English Education Department, 2020)
AbstractNowadays, English is the most important language, including the students who study in STKIP Situs Banten. To be fluent in English students have to increase their ability in writing the paragraph. The Researcher used a flipped classroom learning model since the Covid-19 Pandemic struck Indonesia and the classroom meeting cannot be assessed. This model incorporates dynamic learning; understudy inclusion and present-day innovation by utilizing ICT. In a flipped classroom, the material was given through learning recordings, instructional exercise,s and PowerPoint material by means of WhatsApp group that understudies saw in their homes before the virtual class is acquired. The key objective of this investigation is to explore the practicality of the flipped classroom learning model for teaching paragraph writing. The analyst took the examples from second-semester students in the English instruction division of STKIP Situs Banten. After this activity research measure has been done, this flipped examination lobby learning model can be utilized as a reasonable model for growing understudies limit in section composing. The researcher had dissected that there are a few reasons which drive this occurred: understudy's inspiration, understudy's Writing propensities, students autonomously, and varieties of alluring material. Keywords: Flipped classroom learning model, Information and Computer Technology, Paragraph writing.